Cardiac function in Vimba vimba embryos under electromagnetic exposure at hatchery-relevant intensities - Jan Krzystolik; Adam Tański; Camille L. Musseau (PLoS ONE, 2025)
The increasing expansion of energy infrastructure and anthropogenic transformation of the environment have introduced electromagnetic fields (EMFs) into aquatic ecosystems. While studies on the impact of EMFs on aquatic organisms are growing, their effects on fish embryonic development remain poorly understood. This study investigated the influence of electromagnetic exposure dominated by the magnetic (B) component, measured at 11.15 (± 2.24) μT and 50 Hz, on the heart rate of vimba bream (Vimba vimba) embryos, a species of conservation significance in aquaculture. The electric (E) component was not measured, and its potential contribution cannot be excluded. Fertilized V. vimba eggs were incubated under control conditions or exposed to an EMF, and embryonic heart rate was monitored in two experimental series to assess both short- and long-term EMF effects. In Experiment 1, embryos were incubated either under EMF (Variant B, n = 18) or control conditions (Variant A, n = 18) and observed without additional exposure. In Experiment 2, embryos incubated under EMF (Variant D, n = 30) or control conditions (Variant C, n = 30) were exposed to EMF during microscopic observation. Bayesian non-linear mixed models revealed significant EMF effects in both experiments. Embryos exposed to EMF during incubation (Variant B) displayed a 23.5% higher baseline heart rate (95% CI: 14.5–31.9%) compared to controls. In Experiment 2, embryos exposed to EMF during observation (Variant D) showed a rapid heart rate increase of 29.0% (95% CI: 21.5–37.6%). Embryos exposed to EMF during incubation exhibited a diminished response to subsequent EMF exposure, suggesting physiological adaptation. Additionally, EMF exposure during incubation was associated with reduced inter-individual variability in heart rate, suggesting a homogenizing effect on embryonic cardiac responses. These findings demonstrate measurable cardiac responses of fish embryos to hatchery-relevant electromagnetic exposure and highlight compensatory mechanisms regulating heart rate. While the results suggest fish embryos can adapt to such electromagnetic exposure, further studies are required to disentangle the roles of both magnetic and electric components and to evaluate long-term physiological and ecological consequences.